Spotted Fever Group Rickettsioses (SFGR): weather and incidence in Illinois - KERINS, J. L.; DOREVITCH, S.; DWORKIN, M. S. (Epidemiology and infection, 2017)
The purpose of this study was to identify predictors of increasing incidence of Spotted Fever Group rickettsioses (SFGR) in Illinois, with a specific focus on weather variables. We analysed cases of SFGR reported to the Illinois Department of Public Health from 2004 to 2013. Surveillance definitions changed in 2008 and 2010, but those changes alone did not account for observed spikes in incidence in 2008, 2012 and 2013. A total of 590 cases of SFGR occurred, with the majority in the southernmost portion of the state. Only 3·4% of the reported cases were considered confirmed under the case definition. Increased mean winter temperature (IRR 1·32, CI 1·25–1·40) and increased precipitation (IRR 1·08, CI 1·04–1·11) were each associated with increased incidence of SFGR. Our findings show that weather appears to play a significant role in explaining the increasing annual incidence of SFGR in Illinois.